NUEVO MODELO DE RADIO A TRAVÉS DE LA CUARTA PANTALLA: RADIOVISIÓN, LA RADIO QUE SE VE - Sandra CAVIA FRAILE (Fonseca, Journal of Communication, 2023)
The traditional radio is not strange to the social revolution that Internet and new technologies are raising. In recent years, the fourth screen has led the emergence of new models of radio, including Radiovision. The «radio that you can watch» intends to change and innovate the radio broadcasting media to offer a product that meets the multimedia requirements of users. However, currently, the Radiovision is still at an early stage and it has many aspects that it should improve and care, as the contents and the staging. It is a big chance for the radio that poses challenges and opportunities both for journalism and journalists.